Relativistic configurations of Tolman stellar spheres in f( , ) gravity - Naz, Tayyaba; Malik, Adnan; Gillani, Dania; Mofarreh, Fatemah (International journal of geometric methods in modern physics, 2023)
This study is devoted to investigate the formation of compact stars using Tolman–Kuchowicz space-time in f ( , ) gravity. By taking into account the physically reliable formulations of metric potentials, ξ = B r 2 + 2 ln C and η = ln ( 1 + a r 2 + b r 4 ) , we investigate the equation of motion for spherically symmetric space-time in the presence of an anisotropic matter distribution. Furthermore, matching conditions are employed to compute the unknown constants. By making use of dynamical equations, the pivotal relevant aspects, including energy density, radial and tangential pressures, dynamical equilibrium, anisotropy effect, energy conditions and stability, are physically tested in order to determine the physical acceptability of yielding celestial model, which are thoroughly compared with experimental facts and figures of ten different compact stars. Finally, we observe that obtained anisotropic outcomes are physically viable, free from geometrical and physical singularities. Moreover, these outcomes also provide circumstantial evidence for the existence of super-massive compact stars.